Stereoselective synthesis of γ-hydroxy-α-amino acids through aldolase–transaminase recycling cascades. Issue 39 (3rd May 2017) - Guérard-Hélaine, Christine; Heuson, Egon; Ndiaye, Moussa; Gourbeyre, Léa; Lemaire, Marielle; Hélaine, Virgil; Charmantray, Franck; Petit, Jean-Louis; Salanoubat, Marcel; de Berardinis, Véronique; Gefflaut, Thierry
Abstract : Efficient aldolase (AL)–transaminase (TA) recycling cascades were designed for the stereoselective synthesis of γ-hydroxy-α-amino acids with high atom economy. Abstract : Efficient bi-enzymatic cascades combining aldolases and α-transaminases were designed for the synthesis of γ-hydroxy-α-amino acids. These recycling cascades provide high stereoselectivity, atom economy, and an equilibrium shift of the transamination.l - syn or anti -4-hydroxyglutamic acid andd - anti -4, 5-dihydroxynorvaline were thus prepared in 83–95% yield in one step from simple substrates.